Antibacterial activity of 1 % Roselle flower nano-emulsion extract (Hibiscus sabdariffa) against peri-implantitis-related bacteria on orthodontic mini-implants: An in vitro study - Ridhofar Akbar Khusnul Abdillah; Theresia Indah Budhy; Ida Bagus Narmada; I Gusti Aju Wahju Ardani; Nastiti Faradilla Ramadhani; Ratri Maya Sitalaksmi; Muhammad Luthfi; Ninik Mas Ulfa; Albertus Putera Nugraha; Tengku Natasha Eleena binti Tengku Ahmad Noor; Alexander Patera Nugraha (Journal of Oral Biology and Craniofacial Research)
Objective: The orthodontic mini-implant (OMI) failure often occurs due to the accumulation of peri-implantitis bacteria surrounding it, which results in a stable, resistant form of absolute skeletal anchorage during orthodontic treatment. Administering doxycycline may be the solution, but long-term side effects result in antibiotic resistance. Roselle flowers (Hibiscus sabdariffa) possess beneficial active phytochemical substances, which may have potential as an OMI peri-implantitis alternative therapy. This study investigates the antibacterial activity of 1 % Roselle flower (H. sabdarifa) nanoemulsion (NE) extract (1 % RNE) toward peri-implantitis bacteria in OMIs. Methods: A phytochemical analysis of 1 % RNE was carried out to examine the active substances possessed in it, such as flavonoids, quinone, saponin, alkaloids, tannins, terpenoids, and steroids. Nanoemulsion characterization was carried out using a particle size analyzer (PSA). The antibacterial activity of 1 % RNE toward Prevotella intermedia (Pi), Porphyromonas gingivalis (Pg), Aggregatibacter actinomycetemcomitans (Aa), and Fusobacterium nucleatum (Fn) was carried out to determine the minimum inhibitory concentration, minimum bactericidal concentration, and inhibitory zone compared with doxycycline as a positive control. Results: Roselle flower NE extract (1 %) possessed flavonoids, quinone, saponin, alkaloids, tannins, terpenoids, and steroids positively. The PSA showed that the 1 % RNE had a size of 98.13 d nm. The antibacterial activity of 1 % RNE against Aa, Pg, Pi, and Fn bacteria at 3.125 % showed significant differences (p < 0.05). The antibacterial activity of 1 % RNE toward peri-implantitis bacteria is lower than that of doxycycline. Conclusion: Roselle flower NE extract (1 %) has antibacterial activity against peri-implantitis bacteria at a concentration of 3.125 %.